Biosorption of crystal violet by nutraceutical industrial fennel seed spent equilibrium, kinetics, and thermodynamic studies. (August 2022) - Sulthana, Razia; Taqui, Syed Noeman; Syed, Usman Taqui; Soudagar, Manzoore Elahi M.; Mujtaba, M.A.; Mir, Rayees Afzal; Shahapurkar, Kiran; Khidmatgar, Abdulqhadar; Mohanavel, V.; Syed, Akheel Ahmed; Hossain, Nazia
Abstract: The present research aims to describe a study that would investigate the practicability of using nutraceutical industrial fennel seed spent (NIFSS) is one of the low-cost types of biosorbent which adsorbs a cationic dye, known as crystal violet (CV), from an aqueous solution. The effects of dye adsorption were also investigated: pH, adsorbent dosage, temperature, particle size, and initial dye concentration. Then the experimental equilibrium data attained was analyzed using isotherm models of Langmuir, Freundlich, Jovanovic, Vieth-Sladek, Brouers-Sotolongo, Redlich-Peterson, and Sips. Hence the use of Film diffusion, Pseudo-first-order, Pseudo-second-order, Dumwald-Wagner and Weber-Morris models for kinetic adsorption studies was done. The maximum experimental adsorption capacity, qe, was determined to be 140 mg g −1 at equilibrium conditions in the lab. The maximum adsorption of 166.73 mg g −1 was predicted by the Brouers-Sotolongo isotherm, which had the closest value of correlation coefficient (R 2 ) of 0.987. Pseudo-second order model fits the kinetic data well in this paper. The thermodynamic parameter values such as ΔG°, ΔH°, and ΔS° demonstrated that the adsorption process was non-spontaneous and exothermic. The lower value of ΔH° shows the physical nature of the process. The CV was adsorbed onto NIFSS, as per the evidence by SEM images and FTIR spectra. The possibility of interaction in the CV-NIFSS system is discussed. To remove CV from an aqueous solution, NIFSS is a fast and effective adsorbent. Highlights: Excellent crystal violet adsorption capacity by fennel seed spent. Different adsorption modeling, kinetics, and thermodynamics. Comprehensive characterizations of adsorbate.